The Impact Of Organizational Culture And Organizational Commitment On The Work Motivation Of Employees - Hadinata, Immanuel Michael; Chalidyanto, Djazuly (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
This study aims to determine how the influence of organizational culture and organizational commitment on the work motivation of employees of Surabaya Gotong Royong Hospital. The population of this study was 143 respondents, and the sample used was 60 respondents. The analysis used in this study uses descriptive and multiple linear regression analysis, namely to see the influence, organizational culture and organizational commitment to work motivation. The results of this study show that organizational culture variables and organizational commitment have a positive effect on the work motivation of Surabaya Gotong Royong Hospital employees, both partially and simultaneously.